Mosul University WLAN Security: Evaluation, Analysis and Improvement - Hachum, Omar Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2011)
In this paper, Mosul University Wireless Local Area Network (MUWLAN) security will be evaluated. The evaluation was made to test the confidentiality, integrity and availability of the MUWLAN. Addressing these issues will help in ensuring tighter security. After the evaluation, serious security pitfalls were found that can allow any attacker to have access to the MUWLAN and uses their internet service. Based on the obtained results, suggestions for improvement were made to tighten the security of Mosul University wireless local area network. Keyword : - WLAN security, WEP encryption, PTW attack, Wireshark, MITM attack, SSLStrip attack.